Inhibition of fusidic acid resistance through restricting conformational flexibility in domain III of EF-G - Alexandra Schindl; Megan E. Jones; Leela Ghimire; Arnout P. Kalverda; Gemma Wildsmith; Antonio N. Calabrese; Jennifer H. Tomlinson (Proceedings of the National Academy of Sciences, 2025)
Fusidic acid (FA) is one of few remaining antibiotics active against Methicillin-resistant Staphylococcus aureus . FusB confers resistance to FA by rescuing the translocation factor Elongation Factor-G (EF-G) from FA-stalled ribosome complexes. FusB induces allosteric effects on dynamics in EF-G, causing significant changes in the conformational flexibility of domain III that result in an increase in a minor, more disordered state, overcoming the steric block induced by FA. We show that restraining flexibility in the two central β-strands of EF-G domain III prevents the FusB-induced increase in this minor state population, preventing FusB-mediated release of EF-G from the ribosome and thereby reinstating FA-induced stalling of protein synthesis. We further identify a region controlling access to the minor state population, potentially pinpointing the allosteric mechanism within domain III by which FusB acts. Our findings suggest a possible region that could be targeted for rational design of an inhibitor of FusB-mediated conformational flexibility, reinstating FA sensitivity even in the presence of FusB, which could rejuvenate the efficacy of this clinically important antibiotic.